Reworking the Bible : apocryphal and related texts at Qumran : proceedings of a joint symposium by the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature and the Hebrew University Institute for Advanced Studies Research Group on Qumran, 15-17 January, 2002 - Chazon, Esther G.; Dimant, Devorah.; Clements, Ruth. (Studies on the Texts of the Desert of Judah, 2005)
This book contains papers presented at a symposium on "Reworking the Bible at Qumran" convened in 2002 by the Institute of Advanced Studies and the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature at the Hebrew University of Jerusalem. The core theme is the use and interpretation of the Bible in apocryphal and related works found at Qumran. Nearly half the papers treat legal interpretation; the other half, examines narrative exegesis. Key issues include the question of the authority of the reworked biblical texts, their exegetical techniques, motifs, and genres. This collection provides a valuable resource for the study of Bible, the history of interpretation, apocrypha and pseudepigrapha, ancient Judaism and early Christianity.